DISRUPSI DIGITAL: FENOMENA PROSTITUSI ONLINE DI DAERAH PENERAPAN SYARI’AT ISLAM - Mirza Fanzikri; Siti Nur Zalikha; Tri Mairina Hamdani; Sonia Sonia (Al-Ijtima`i: International Journal of Government and Social Science, 2023)
Digital developments, expected to contribute to efficiency and ease in the development process, are often used reversely. Specific communities also use digital technology as a means of communication and information in carrying out practices that violate norms and laws. In Aceh Province, which incidentally is the implementation area of Islamic Shari'at, the use of digital is used in practices that violate the Qanun (regional regulation) of Islamic Shari'at. Prostitution, one of the criminal cases of Islamic Sharia, was found that all perpetrators revealed that they carried out these 'unlawful' transactions through online media. This study aims to explain the driving factors for prostitution behavior and explain the government's collaborative efforts in dealing with online prostitution in Aceh. This study uses a qualitative approach that descriptively describes the primary and secondary data. Preliminary data were obtained through interviews and observation techniques, while secondary data was obtained through document review. Data analysis was passed through classification, reduction, and conclusion. The study results show that the driving factor for the dominant prostitution behavior is motivated by personal desires. In addition, it is also caused by environmental and lifestyle factors, the economy, family problems, as well as experiences of sexual harassment, and the loss of virginity. The government's collaborative efforts in dealing with online prostitution are carried out by controlling prostitution. The government and other elements of society conduct routine raids and patrols and hold outreach to the community down to the community level.